Sosialisasi Warga Sekitar Lahan Cilobak Terkait Optimalisasi Dan Alih Fungsi Lahan Menjadi Taman Budidaya Hortikultura Yang Produktif Dan Bernilai Jual TinggiI - Maliq, Alita Aulia; Saragih, Maltha Malinda Thea; Ramadhanti, Syafira; Mulyadi, Mulyadi; Lewoleba, Kayowuan Kayus; Atiyyah, Rifa; Manalu, Ronald; Marza, Suci Eryzka (Jurnal Ilmiah Wahana Pendidikan, 2024)
Horticulture is one of the potentials in Cilobak land. The target partners at the location are residents who work at home, unemployed, and kids. Community empowerment in Cilobak land, Cinere Subdistrict, Depok City is motivated by the low understanding of horticulture so that there is a land vacancy which results in new problems, such as land abuse and disruption of aesthetic value. The misuse of land in question includes the use of land as a location for crime, immoral acts, and garbage disposal. This community empowerment aims to increase residents' awareness, skills, and knowledge about land conversion so that related problems can be resolved. In addition, the conversion of land into a horticultural garden can also improve the economy of residents through land productivity. The output target of this activity is to increase knowledge and skills, awareness, and motivate target partners in utilizing vacant land for horticultural gardening both in conventional and hydroponic media. The participatory method was used to actively involve partners in the implementation of horticultural training. The results of the activities that have been carried out include training in horticultural planting methods and techniques from seeding, knowledge of planting media, fertilizers, plant nutrition, pests, and plant diseases to production methods so that they can generate economic value and help food security at home. The community service program that has been implemented helps target partners solve problems and increase the productivity of target partners.